The Effect of Originally Designed Innovative Activities on Students’ Innovative Thinking Tendencies and Students’ Views on the Process - Akçam, Sümerya; Güven Yıldırım, Ezgi; Önder, Ayşe Nesibe (Bulletin of Educational Studies, 2024)
The aim of this study is to investigate the effect of an inquiry-based learning method supported by innovative activities on students’ innovative thinking tendencies in teaching the 7th grade “Force and Energy” unit. Another aim of the study is to determine the opinions of the experimental group of students who were taught innovative activities about the process. In order to obtain the data for the purpose of the study, an explanatory design, which is one of the mixed research methods in which quantitative and qualitative research methods are used together, was used. As a result of the study, it was found that there was a statistically significant difference in favor of the experimental group between the “Innovative Thinking Tendency Scale” scores of the students in the experimental and control groups after the application. When the answers given by the students to the interview questions directed to them are analyzed, in the first question, students defined innovative individuals as curious, well-intentioned, careful, respectful, patient, self-confident, intelligent, thinking, having the ability to design and criticize, using their minds, attentive, finding impressive ideas, and putting forward plausible ideas. In the second question, students stated that the use of innovative activities in the Force and Motion unit had effects such as facilitating learning, understanding the subject better, enabling thinking, providing permanent learning, and enabling visualization. In third question, the students talked about the advantages and disadvantages of these activities. Also, with last question students talked about both positive and negative aspects of the process.